Progress and Prospects of Nanocellulose-Based Membranes for Desalination and Water Treatment - Asif Saud; Haleema Saleem; Syed Javaid Zaidi (Membranes, 2022)
Membrane-based desalination has proved to be the best solution for solving the water shortage issues globally. Membranes are extremely beneficial in the effective recovery of clean water from contaminated water sources, however, the durability as well as the separation efficiency of the membranes are restricted by the type of membrane materials/additives used in the preparation processes. Nanocellulose is one of the most promising green materials for nanocomposite preparation due to its biodegradability, renewability, abundance, easy modification, and exceptional mechanical properties. This nanocellulose has been used in membrane development for desalination application in the recent past. The study discusses the application of membranes based on different nanocellulose forms such as cellulose nanocrystals, cellulose nanofibrils, and bacterial nanocellulose for water desalination applications such as nanofiltration, reverse osmosis, pervaporation, forward osmosis, and membrane distillation. From the analysis of studies, it was confirmed that the nanocellulose-based membranes are effective in the desalination application. The chemical modification of nanocellulose can definitely improve the surface affinity as well as the reactivity of membranes for the efficient separation of specific contaminants/ions.